2011
DOI: 10.1002/app.33621
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of the biomaterial poly(lactic acid‐coNε‐carbobenzoyloxy‐L‐lysine) via direct melt copolymerization

Abstract: With D,L‐lactic acid and Nϵ‐carbobenzoyloxy‐L‐lysine [Lys(Z)] as the starting monomer material and tin dichloride as the catalyst, the drug carrier material poly(lactic acid‐co‐Nϵ‐carbobenzoyloxy‐L‐lysine) was synthesized via direct melt polycondensation. The copolymer was systematically characterized with intrinsic viscosity testing, Fourier transform infrared spectroscopy, 1H‐NMR, gel permeation chromatography, differential scanning calorimetry, and X‐ray diffraction. The influences of different feed molar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…It can be seen that, compared with the homopolymer PDLLA, most copolymer samples have smaller molecular weight. This indicates that the introduction of PTA as a monomer containing the reactive amino is not beneficial to the direct melt copolymerization, and this conclusion is similar with the reported before . However, only sample C3 has bigger M n and M w than PDLLA synthesized under the same reaction conditions, this is related to the formation of multi‐core structure in copolymer, which will be discussed in the following.…”
Section: Resultssupporting
confidence: 86%
“…It can be seen that, compared with the homopolymer PDLLA, most copolymer samples have smaller molecular weight. This indicates that the introduction of PTA as a monomer containing the reactive amino is not beneficial to the direct melt copolymerization, and this conclusion is similar with the reported before . However, only sample C3 has bigger M n and M w than PDLLA synthesized under the same reaction conditions, this is related to the formation of multi‐core structure in copolymer, which will be discussed in the following.…”
Section: Resultssupporting
confidence: 86%
“…Firstly, different catalysts, such as protonic acid, metal oxides, and metal halides are screened (Table 1). It can be observed that, among five available catalysts usually used in the direct melt homo-/co-polymerization of LA, [28,31,37,40,44] the reaction catalyzed by stannous oxide (SnO) gives the biggest molecular weight (run 2). Thus, SnO is selected as the catalyst in the following experiments.…”
Section: Optimal Synthetic Conditions For Plaambmentioning
confidence: 99%
“…According to the previous works on melt copolymerization of LA [18][19][20][21][22], LA and DAB should be prepolymerized before copolymerization. After LA and DAB were uniformly mixed as preplanned molar feed ratio, the mixture was directly dehydrated for 8 h at 140°C under 4000 Pa in a flask equipped with mechanical stirring and thermometer.…”
Section: Preparation Of P(la-co-dab)mentioning
confidence: 99%
“…There are many compounds used as catalysts in LA melt polymerization, e.g. proton acids, metal oxides, metal halides, and so on [21][22][23][24][25][26][27]. Here, five common compounds are selected as catalysts, and their influences on the reaction are shown in Table 1.…”
Section: Optimal Synthesis Conditionsmentioning
confidence: 99%
See 1 more Smart Citation